Antenna design using left-handed materials - Abd. Rahman, Tharek; Abdolee, Reza (Faculty of Electrical Engineering, 2008)
Smart antenna technologies are emerging as an innovative way to meet the growing demand for more powerful, cost-effective and highly efficient wireless communication systems. In this project, from broad category of smart antenna techniques, the switch beam digital-beamforming technique in the downlink is deployed to improve the fidelity and performance of WiMax application. In this regards, the designed system forms and steer the beam according to the user location which is known to the system. In addition, the system performs sidelobe cancellation base on the chebyshev algorithm to optimize the antenna radiation pattern. The design and implementation steps are as follow: the system is firstly modeled by MATLAB software. After modeling, the algorithm is implemented in DSP by using C and Code Composer Studio. After DSP hardware implementation, the signal management is performed in DSP before transmission to the FPGA board. This management is necessary, in order to make processed signal in DSP suitable for channel separation process in FPGA. FPGA is deployed to split the data stream into sixteen channels corresponding to number of antenna elements. Next, the FPGA and DSP are integrated together to form the baseband switch beam smart antenna system. After integration process, the hardware is tested; the results prove that the system functions properly as we expected from simulation model. In this project, lastly, the initial design of IF, RF-front-end and their necessary circuits are also portrayed to be used in the next smart antenna research project.